Effects of Shear Rate and Inhibitors on Wax Deposition of Malaysian Crude Oil - Norida, Ridzuan; Fatmawati, Adam; Zulkefli, Yaacob (Oriental Journal of Chemistry, 2015)
Wax deposition can cause a serious problem in crude oil flow assurance, especially in deep water operation due to the long chain of n-paraffin. This paper examines the effects of two factors on the deposition process, which are shear rate and different types of inhibitors. 10 mL of four different types of wax inhibitors (cocamide diethanolamine (C-DEA), diethanolamine (DEA), poly(ethylene-co-vinyl acetate) (EVA) and poly (maleic anhydride-alt-1-octadecene) (MEA) were injected into a crude oil vessel where the temperature of cold finger and water bath were set at 5°C and 50°C, respectively. The rotation speed was operated at different ranges between 0 and 600 rpm. From the result, it was found that the amount of total wax deposit decreased when shear rate increased. EVA showed a strong effect to inhibit wax formation with 33.33% reduction of wax deposit at 400 rpm as compared to other inhibitors.